2019
DOI: 10.1016/j.contraception.2018.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal intent and postpartum receipt of long-acting reversible contraception among women receiving medication-assisted treatment for opioid use disorder

Abstract: Despite prenatal interest in using LARC, most pregnant women with OUD on MAT did not receive postpartum LARC. The provision of immediate postpartum LARC services may reduce barriers to postpartum LARC receipt such as poor attendance at the postpartum visit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 22 publications
0
18
1
Order By: Relevance
“…29 In fact, one institution that did not previously offer immediate postpartum LARC insertion noted that while there is interest and intent in LARC use in women with OUD, many women did not receive them in the interval period. 24 We also found that older women more often chose tier 1 contraceptive methods. This is likely due to the choice of sterilization in women who have satisfied parity.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…29 In fact, one institution that did not previously offer immediate postpartum LARC insertion noted that while there is interest and intent in LARC use in women with OUD, many women did not receive them in the interval period. 24 We also found that older women more often chose tier 1 contraceptive methods. This is likely due to the choice of sterilization in women who have satisfied parity.…”
Section: Discussionmentioning
confidence: 60%
“…22 This is in contrast to 14% LARC use rates reported in the general population. 23 Low uptake of contraception in opioid using women has been attributed to numerous factors, including poor postpartum visit attendance, 3,24,25 stigma and fear of losing custody of their child(ren), 26 lack of information regarding both LARCs and short-acting methods, 27 and misunderstanding of their fertility. 3,28 Interestingly, we also found that more than half of women with self-reported opioid use in our study chose immediate tier 1 method uptake, of which Data are represented as n (%), unless noted as means in which case it is meanstandard deviation.…”
Section: Discussionmentioning
confidence: 99%
“…41 Intent to initiate these methods is dependent on antepartum contraception discussions. 42 For all these reasons, antepartum contraception counseling is vital to postpartum contraceptive usage. [15][16][17][18][19][20][21][22][23] While this study captures a large sample size of diverse women including both high-and low-risk women, there are some limitations.…”
Section: Discussionmentioning
confidence: 99%
“…39 For example, one retrospective study of pregnant women with opioid use disorder receiving MAT (n = 791) found that approximately one-third of women (35%) intended to use postpartum LARC, but of those, only 45% of women attended the postpartum visit and <20% received the contraceptive. 40 This is not unique to women who use opioids, as ≈ 10% to 40% of all women do not attend the postpartum visit, and 40% to 75% of women who plan to use a postpartum IUD do not obtain it. [41][42][43] However, the American Congress of Obstetricians and Gynecologists recommends immediate postpartum LARC as a contraceptive option for all women, particularly women who use opioids, due to a lower rate of contraceptive use and higher rate of unplanned pregnancies than women who do not use opioids.…”
Section: Costmentioning
confidence: 99%
“…Women may avoid accessing medical care or family planning services outside of their substance use disorder treatment facility because of logistical challenges such as lag times in getting an appointment and difficulties in attending referral appointments 39 . For example, one retrospective study of pregnant women with opioid use disorder receiving MAT (n = 791) found that approximately one‐third of women (35%) intended to use postpartum LARC, but of those, only 45% of women attended the postpartum visit and <20% received the contraceptive 40 . This is not unique to women who use opioids, as ≈ 10% to 40% of all women do not attend the postpartum visit, and 40% to 75% of women who plan to use a postpartum IUD do not obtain it 41–43 .…”
Section: Factors Affecting Contraceptive Accessmentioning
confidence: 99%